Sex Chromosome-wide Transcriptional Suppression and Compensatory Cis-Regulatory Evolution Mediate Gene Expression in the Drosophila Male Germline. - Emily L Landeen; Christina A Muirhead; Lori Wright; Colin D Meiklejohn; Daven C Presgraves (PLoS Biology, 2016)
The evolution of heteromorphic sex chromosomes has repeatedly resulted in the evolution of sex chromosome-specific forms of regulation, including sex chromosome dosage compensation in the soma and meiotic sex chromosome inactivation in the germline. In the male germline of Drosophila melanogaster, a novel but poorly understood form of sex chromosome-specific transcriptional regulation occurs that is distinct from canonical sex chromosome dosage compensation or meiotic inactivation. Previous work shows that expression of reporter genes driven by testis-specific promoters is considerably lower-approximately 3-fold or more-for transgenes inserted into X chromosome versus autosome locations. Here we characterize this transcriptional suppression of X-linked genes in the male germline and its evolutionary consequences. Using transgenes and transpositions, we show that most endogenous X-linked genes, not just testis-specific ones, are transcriptionally suppressed several-fold specifically in the Drosophila male germline. In wild-type testes, this sex chromosome-wide transcriptional suppression is generally undetectable, being effectively compensated by the gene-by-gene evolutionary recruitment of strong promoters on the X chromosome. We identify and experimentally validate a promoter element sequence motif that is enriched upstream of the transcription start sites of hundreds of testis-expressed genes; evolutionarily conserved across species; associated with strong gene expression levels in testes; and overrepresented on the X chromosome. These findings show that the expression of X-linked genes in the Drosophila testes reflects a balance between chromosome-wide epigenetic transcriptional suppression and long-term compensatory adaptation by sex-linked genes. Our results have broad implications for the evolution of gene expression in the Drosophila male germline and for genome evolution.